The Role of β Blockers in the Management of Hypertension - Moser, Marvin (J Clin Hypertens (Greenwich), 2007)
Following a hypertension symposium in New York City on February 2, 2005, a roundtable was convened to discuss the use of β blockers in the management of hypertension. Dr. Marvin Moser, Clinical Professor of Medicine at the Yale University School of Medicine, New Haven, CT, moderated the discussion. Participating in this roundtable were Dr. Thomas Pickering, Professor of Medicine at the Columbia University School of Medicine, New York, NY, and Dr. William Cushman, Professor of Preventive Medicine and Medicine at the University of Tennessee College of Medicine, Memphis, TN.